Penerapan Model Discovery Learning Menggunakan Pendekatan Saintifik Untuk Meningkatkan Keaktifan Belajar IPA Peserta Didik Kelas V SDN 109/II Manggis Kabupaten Bungo - Aldino Aldino; Arisman Sabir; Yanti Murni Murni; Fitri Yanti; Raja Bani Pilitan (Departement of Mathematics Education, 2024)
The learning process in the 2013 curriculum is carried out with students being the center of learning, so that students have a role to be able to be more active in the learning process. Natural Sciences (IPA) is learning content related to the process of searching for something systematically and in accordance with the results of discoveries. Science learning is not just about learning concepts, principles or mastery of knowledge in the form of facts, but in science it is known as the process of discovery. Based on the results of initial observations carried out at SDN 109/II Manggis Kab. Bungo on January 20 2022 obtained information related to the learning process in the science learning content in class V which was carried out at the school, which did not show that all students were actively involved in the learning process. The type of data used is Classroom Action Research (PTK) using qualitative and quantitative data. The subjects in this research were all students and teachers of class V at SDN 103/II Manggis, Bungo Regency, even semester of the 2023/2024 academic year. Data collection using interviews is a data collection technique carried out to obtain in-depth information from sources. Based on the results of the research, it shows that through the application of the Discovery Learning model with a Scientific Approach, it has a good impact on increasing students' learning activeness in science content, as can be seen from the increase in students' learning activeness in science from pre-action, namely by 23.07% until at the end of cycle II it increased to 84 .61%. Increasing students' learning activity occurs periodically from cycle I to cycle II by applying the Discovery Learning model syntax, namely stimulation, problem statement (problem identification), data collection, data processing, verification (proof) and generalization (drawing conclusions) and the Scientific Approach with the elements of observing, asking, collecting information/trying, reasoning/associating and communicating.